PENGEMBANGAN KNOWLEDGE MANAGEMENT SYSTEM BERBASIS SECI UNTUK BEMU UNIVERSITAS MA CHUNG - Aaron Christoperus Prayogo Lauw; Christian Difae Klemens (Universitas Ma Chung, 2025)
Organizational knowledge in the Student Executive Board of Ma Chung University is often lost during leadership transitions. This study aims to develop a web-based Knowledge Management System (KMS) to document and share organizational knowledge in a structured and sustainable manner. The research design follows a Research and Development (R&D) approach using the SECI (Socialization, Externalization, Combination, Internalization) model. Data collection was conducted through observation, interviews, and literature review. The needs analysis informed the design of system features such as document management, membership, work programs, student complaints, a knowledge portal, and admin dashboard. The system was implemented using a web platform and tested through functionality testing and user evaluation. The results show that the system successfully documented explicit knowledge such as SOPs and templates, and converted tacit knowledge from students into structured data through the complaint feature. The SECI model enabled a continuous and well-documented knowledge cycle. The conclusion of this study is that the developed KMS improves the efficiency of knowledge management and reduces the risk of information loss. The system also provides a foundation for future development of features such as discussion forums or content analysis..